2021
DOI: 10.1177/0022042621994547
|View full text |Cite
|
Sign up to set email alerts
|

Why Parents Misuse Prescription Drugs to Enhance the Cognitive Performance of Healthy Children: The Influence of Peers and Social Media

Abstract: The mechanisms affecting parents’ misuse of prescription stimulant drugs to boost healthy children’s school performance are hardly unknown. Using four web-based factorial vignette surveys (2×2 between-subjects design experiment), we investigated the willingness of U.S. parents with school-aged children to medicate a fictitious 13-year-old child whose grades had declined. We examined mechanisms of informational and normative social influence on their decision-making: others’ behavior ( NExperiment 1 = 359), oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 114 publications
0
4
0
Order By: Relevance
“…Keberlanjutan, di sisi lain, menunjukkan pemeliharaan kemajuan dalam tingkat optimal yang dapat dicapai. Secara umum, istilah "perkembangan" mencakup proses pertumbuhan, penyesuaian, dan transformasi sepanjang kehidupan, meliputi dimensi fisik, kepribadian, sosio-emosional, kognitif, dan bahasa (Ahmad, 2019;Koniakou, 2022;Reisdorfer, 2023;Sattler, 2021). Ketika diterapkan pada anak-anak, perkembangan merujuk pada proses bertahap pembentukan karakteristik dan sifat yang dipengaruhi secara biologis ketika mereka belajar melalui pengalaman (Handayani & Maharani, 2022).…”
Section: Pendahuluanunclassified
“…Keberlanjutan, di sisi lain, menunjukkan pemeliharaan kemajuan dalam tingkat optimal yang dapat dicapai. Secara umum, istilah "perkembangan" mencakup proses pertumbuhan, penyesuaian, dan transformasi sepanjang kehidupan, meliputi dimensi fisik, kepribadian, sosio-emosional, kognitif, dan bahasa (Ahmad, 2019;Koniakou, 2022;Reisdorfer, 2023;Sattler, 2021). Ketika diterapkan pada anak-anak, perkembangan merujuk pada proses bertahap pembentukan karakteristik dan sifat yang dipengaruhi secara biologis ketika mereka belajar melalui pengalaman (Handayani & Maharani, 2022).…”
Section: Pendahuluanunclassified
“…Mihailov et al ( 2021 ) report how people deem cognitive enhancement less morally wrong if widely used. Peer behavior and experiences are valuable sources of information for considering whether to engage with an enhancement (Sattler et al, 2021 ). The disruptive potential of Human Enhancement seems to be problematic only insofar as enhancements remain external to established practices.…”
Section: Disentangling the Phenomenonmentioning
confidence: 99%
“…Directly concerned with human behavior and mind, Human Enhancement seems like an ideal phenomenon for psychology to investigate. Indeed, there is a rich body of literature on the concerns and motivations underlying Human Enhancement efforts (e.g., Hotze et al, 2011 ; Pew Research Center, 2016 ; Sample et al, 2020 ; Sattler et al, 2021 ; Sattler et al, 2014 ; Scheske and Schnall, 2012 ). But the latest literature neglects to acknowledge the intricate and multifaceted nature of the technologies employed in Human Enhancement and their transformative effects concerning various aspect of human capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…To meet these expectations, parents increasingly engage in intense parenting practices such as private tutoring (Wells et al, 2016 ). Researchers also highlight the susceptibility of parents to rationalize the non-medical use of prescription stimulants as an instrument to achieve their parenting goals, a relatively new debated and potentially health-endangering practice (Arria & DuPont, 2010 ; Sattler et al, 2021 ). Such non-medical use of prescription drugs specifically aimed at enhancing “mental functioning beyond what is necessary to sustain or restore good health” has been termed cognitive enhancement (CE) (Dresler et al, 2013 , p. 29).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, most parents perceive CE as dangerous for their children and feel responsible to avoid harm (Ball & Wolbring, 2014 ; Forlini & Racine, 2009 ). Nevertheless, a recent study involving U.S. American parents found that information on social media about the benefits of CE-drugs can increase parents’ willingness to give such drugs to children (Sattler et al, 2021 ). Further, if others engage in such practices, the perceived pressure to act similarly can increase (Maher, 2008 ).…”
Section: Introductionmentioning
confidence: 99%